Myasthenia Gravis and Myasthenic Disorders. - Engel, Andrew G. (Contemporary Neurology Series, 81., 2012)
Myasthenia Gravis and Myasthenic Disorders, Second Edition is a thoroughly re-written and updated version of the highly successful first edition published in 1999. The current edition begins with an overview of the anatomy and molecular architecture of the neuromuscular junction and the electrophysiologic diagnosis of its disorders. The introductory chapters are followed by a detailed exposition of the pathogenesis, natural history, diagnosis and therapy of the autoimmune myasthenias, the Lambert-Eaton myasthenic syndrome, and the increasingly complex and fascinating diseases collectively refe.